2004
DOI: 10.1016/j.jasms.2004.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative determination of the selectivities of five different phenyl radicals in hydrogen atom abstraction from ethanol

Abstract: An experimental method is described for obtaining quantitative selectivity information for H-atom abstraction by organic radicals from different sites of a substrate in the gas phase. The method is used to determine the selectivities of five different phenyl radicals toward the three different types of hydrogen atoms in ethanol. This experimental method involves studying the reactivities and selectivities of derivatives of the radicals that contain a chemically inert, charged group (distonic ions), which allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 24 publications
(8 reference statements)
5
29
0
Order By: Relevance
“…Previous studies of positively charged phenyl radicals in the gas phase have shown that the selectivity of hydrogen atom abstraction from ethanol is related to the EAs of the radicals. 47 Radicals with a lower EA (indicating lower reactivity) tend to attack the CH 2 -group rather than the CH 3 -group of ethanol because the CH 2 -group has a lower homolytic C-H bond dissociation energy. Indeed, in the gas phase, the hydrogen atom abstraction efficiency from methanol is 1.7 % and 0.4 % for the protonated 3- and 4-isomers, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies of positively charged phenyl radicals in the gas phase have shown that the selectivity of hydrogen atom abstraction from ethanol is related to the EAs of the radicals. 47 Radicals with a lower EA (indicating lower reactivity) tend to attack the CH 2 -group rather than the CH 3 -group of ethanol because the CH 2 -group has a lower homolytic C-H bond dissociation energy. Indeed, in the gas phase, the hydrogen atom abstraction efficiency from methanol is 1.7 % and 0.4 % for the protonated 3- and 4-isomers, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Because the ionic avoided curve crossing model (described above) predicts that the reaction efficiencies should also depend on the difference between the IE of the hydrogen-atom donor and the EA of the aryl radical (i.e., (IE – EA)), it was of interest to examine this relationship by using several different aryl radicals and hydrogen-atom donors. Thus, reaction efficiencies (measured here for cyclohexane and isopropanol, or measured previously) for hydrogenatom abstraction from ethanol by seven different aryl radicals ( g , k , l , n , q , s , t ),61,76 from tetrahydrofuran by twenty different aryl radicals ( b , c , d , e , f , g , h , i , j , l , m , q , s , t , aa , bb , cc , dd , ee , ff ),22,23,27,28,63 and from 2-methyltetrahydrofuran by eleven different aryl radicals ( b , d , e , f , h , i , j , m , s , aa , bb ),23 were studied. The calculated (IE – EA) values and the reaction efficiencies for hydrogen-atom abstraction are listed in Table 5.…”
Section: Resultsmentioning
confidence: 99%
“…However, the calculated reaction enthalpies (ΔH rxn ) associated with the hydrogen atom abstraction reactions of charged radicals 2 – 4 with methanol and ethanol (Table 3) do not reflect the observed differences in the reaction rates with these two neutral reagents. For example, ΔH rxn for hydrogen atom abstraction from the α-carbon in ethanol48 by 2 is only 0.2 and 3.3 kcal/mol more exothermic than those for 3 and 4 (ΔH rxn ; −25.6, −25.4 and −22.3 kcal/mol, respectively; Table 3), yet the reaction efficiency for hydrogen atom abstraction by 2 (33%; Table 1) differs from that of 3 (11%) by a factor of three and from that of 4 (4.2%) by a factor of about eight. Similar trends are also observed for methanol (Tables 1 and 3).…”
Section: Discussionmentioning
confidence: 99%